The Effect of Audit Committee Activities, Internal Audit Personnel, and Company Complexity on Audit Fees - Alamsyah, Andrea; Januarti, Indira (Universitas Muhammadiyah Surakarta, 2024)
The determination of the amount of audit fees paid by companies to public accountants can be influenced by various factors. This study aims to examine the effect of audit committee activity, internal audit personnel, and company complexity on audit fees. The research population is manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The total research sample was 165 observation data. The analysis tool uses multiple linear regression. The results showed that company complexity and internal audit personnel had a positive effect on audit fees. Meanwhile, the audit committee activity variable has no positive effect on audit fees. Thus the KAP selection method uses a demand approach. The implications of this study indicate that the selection of KAP tends to be reputable so that no matter how good the supervision carried out by the audit committee or internal audit personnel, the audit fees will also remain high.